UPAYA MENINGKATKAN HASIL BELAJAR GERAK DASAR LOMPAT MELALUI MODIFIKASI PERMAINAN TRADISIONAL ENGKLEK PADA SISWA KELAS II SD NEGERI 2 JERUK KABUPATEN BLORA TAHUN 2013/2014 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
It is expected that, through modification of the traditional hopscotch game learning outcomes of students in learning basic movement can jump. This study uses action research. In the implementation consists of two cycles. Each held one meeting cycle consisting of four stages, namely : planning, action, observation, and reflection. Instrument used in this study is the test performance of students, student activity sheets observation, and written tests (cognitive). Based on the results, the results of the percentage of mastery of learning outcomes in the first cycle, students who scored as much as 55 % complete (11 students) and who did not complete as much as 45 % (9 students). In the second cycle students who scored as much as 90 % complete (18 students) and students who did not complete as much as 10 % (2 students). While the average value in the classroom learning basic movement jump in the first cycle was 68,50. In the second cycle increased to 76,97 . Based on the above results, it can be concluded that the modification of the game hopscotch jump in learning basic movement can improve learning outcomes and down motion on the basis of the second grade students of Jeruk Elementary School Blora.